Metabolic dysfunction-associated fatty liver disease (MAFLD) in the adult population attending a health check-up program in Thailand: prevalence and fibrosis status - Supinya Sono; Apichat Kaewdech; Chutimon Wongsawanon; Thatchaphon Varanuntakul; Tian Jarupanich; Nichakan Sritanabutr; Papontee Ruangtanthawat; Monchusa Phanukasemsin; Lipikar Inchan; Naichaya Chamroonkul; Pimsiri Sripongpun (Scientific Reports)
Abstract Metabolic dysfunction-associated fatty liver disease (MAFLD) poses a significant public health challenge. Guidelines recommend primary care physicians use noninvasive tests to assess advanced fibrosis risk and refer at-risk individuals to hepatology specialists. This study examines the prevalence of MAFLD, fibrosis status, and referral rates in Thailand to enhance the regional care system and provide population-level insights. A cross-sectional study was conducted between 2019 and 2023 at a tertiary care hospital in southern Thailand. We included individuals aged ≥ 18 years undergoing health check-up programs that involved abdominal ultrasound and blood tests. Demographics, clinical variables, and referral information were recorded. The BMI and waist circumference (WC) cutoffs for Asians were used. Liver fibrosis was assessed using the FIB-4 index. A total of 5995 individuals were eligible. The prevalence of fatty liver was 45.2%, with 98.6% of those cases meeting the criteria for MAFLD. The prevalence of fatty liver was significantly higher among older individuals, males, those with larger WC, elevated fasting glucose, lower high-density lipoprotein cholesterol, higher low-density lipoprotein cholesterol, and elevated aspartate and alanine aminotransferase levels (p < 0.01). The prevalence of advanced fibrosis, determined by the FIB-4 > 2.67, was 1.6%. However, only 20% of patients requiring specialized care were referred to specialists. In summary, the prevalence of MAFLD in southern Thailand was 44.6% and advanced fibrosis was found in 1.6% of all MAFLD. Despite requiring specialized care in certain patients, referral rates were quite low. There is a significant opportunity for improving the clinical care and management of MAFLD in this region.